Culture and sensitivity pattern of aerobic bacterial isolates in diabetic foot infections, in a suburban tertiary care hospital in Mumbai - Degloorkar, Sarang; Shah, B. C.; Patel, Kinjal (International Surgery Journal, 2021)
Background: The most common complication observed in patients with diabetes mellitus is diabetic foot infection; it is the bone or soft tissue infection below the malleoli. The most common pathogens involved in this infection are Staphylococcus species and beta haemolytic streptococci. Severe, chronic, or formerly dealt with infections are usually polymicrobial. Hence, the aim of the study was to understand the microbiological profile and antimicrobial susceptibility pattern of pathogens causing diabetic foot infections. Methods: Post approval from Institutional Ethics Committee, a retrospective study was carried out based on review of records of 117 patients with diabetic foot infections over two-year period from 2018 through 2019. All demographical and microbiological data was analysed. Results: Out of 117 patients of diabetic foot infections, 71 (60.68%), patients showed bacterial growth. Amongst 71 patients 45% of patients had gram positive infection. 52% patients had gram negative infection. 3% patients had poly-microbial growth. Most common organism isolated were Staphylococcus aureus 28%, Morgaellamorgagni 11%, Proteus mirabilis 9%, Citrobacter koseri 8%, E. coli 8%. Incidence of Staphylococcus aureus (MRSA and MSSA) was 3% each. Staphylococcus aureus had sensitivity to Rifampicin, Cefoperazone, Tigecycline. Conclusions: Diabetic foot infections are common complication worldwide. Understanding the microbiology will help to deal better in management and prognosis of patients. Hence, it is mandatory to characterize the causative agents, and its antimicrobial susceptibility pattern to ensure successful outcome of diabetic foot infections.